2020
DOI: 10.3168/jds.2020-18330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dairy by-products as milk replacers on quality attributes of ice cream

Abstract: The aim of this study was to evaluate the effect of ricotta whey (RW), cheese whey (CW), and butter whey (BUW) as replacers of whole milk (WM) at different ratios (0:100, 25:75, 50:50, 75:25, and 100:0) in the physicochemical and sensory qualities of ice cream. All formulations, including a commercial sample used as reference, were analyzed for nutritional composition, energy value, pH, titratable acidity (TA), melting behavior, desorption index, instrumental color properties, instrumental hardness, and consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…The results showed that the mean initial pH of the frozen yogurt F0 was higher than those of inulin-containing formulations (P<0.05) (Table 2). Our findings are consistent with those observed by MENESES et al (2020), who attributed the variation detected to the type and level of LCW added. Yet, the frozen yogurt samples with the highest inulin content (F2 and F3) had mean initial values of titratable acidity significantly higher than the other formulations (F0 Figure 2 presents the variations in the values of pH and titratable acidity in the frozen yogurt formulations during the 120 days of storage at -18 °C.…”
Section: Ph and Titratable Acidity During Storage Periodsupporting
confidence: 93%
See 2 more Smart Citations
“…The results showed that the mean initial pH of the frozen yogurt F0 was higher than those of inulin-containing formulations (P<0.05) (Table 2). Our findings are consistent with those observed by MENESES et al (2020), who attributed the variation detected to the type and level of LCW added. Yet, the frozen yogurt samples with the highest inulin content (F2 and F3) had mean initial values of titratable acidity significantly higher than the other formulations (F0 Figure 2 presents the variations in the values of pH and titratable acidity in the frozen yogurt formulations during the 120 days of storage at -18 °C.…”
Section: Ph and Titratable Acidity During Storage Periodsupporting
confidence: 93%
“…The characteristics of the products depend on the composition of the raw material and processing conditions. Thereby, the nutritional composition, texture, melting behavior, and sensory attributes of ice cream can be influenced by the use of dairy whey (SKRYPLONEK et al, 2019;MENESES et al, 2020). Furthermore, there is a lack of data regarding the use of LCW as a total or partial milk substitute in dairy products, which is a substantial challenge for the industry.…”
Section: Santos Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of apple fiber in our study reduced the hardness of ice cream compared to ice cream with inulin only, but these differences were not significant. According to Bahram-Parvar et al [ 71 ], hardness is a parameter that indicates the smoothness and wateriness of ice cream samples [ 92 ]. In our research, the smoothness of ice cream was significantly influenced by the addition of apple fiber, which reduced the feeling of smoothness and creaminess during consumption, increasing their sandiness at both times.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with our results, Cortellino and Rizzolo [9] observed that the addition of 30% ricotta cheese whey did not affect the aroma and overall liking of apple juice. Meneses et al [33] concluded that ricotta and cheese wheys ranging from 25% to 75% did not affect the ice creams' overall liking. On the other hand, Sakhale et al [16] evaluated dairy beverages developed with cheese whey and mango juice at different ratios (70:30, 75:25, and 80:20) and reported a decrease in flavor and overall liking by the increase of cheese whey.…”
Section: Consumer Acceptancementioning
confidence: 99%